(untitled) (CIPEEX, 2022)
THE ENVIRONMENTAL LICENSING PROCEDURE IS AN INSTRUMENT OF THE NATIONAL ENVIRONMENT POLICY THAT OPERATES IN THE MAINTENANCE AND PRESERVATION OF BIODIVERSITY, WITH THE OBJECTIVE OF BRINGING ABOUT HARMONY BETWEEN ECONOMIC ADVANCES AND NATURAL RESOURCES. THE MAIN PURPOSE OF THE WORK IS TO PRESENT THE FLEXIBILITY OF ENVIRONMENTAL LICENSING IN GOIS WITH THE ENACTMENT OF NEW LAWS AND THEIR RELATIONSHIP WITH SUSTAINABLE DEVELOPMENT, AS WELL AS DEMONSTRATING THE LIKELY IMPACTS THAT THIS NEW LICENSING MODEL CAN BRING TO SOCIETY AND THE ENVIRONMENT. THUS, BEARING IN MIND THAT THIS IS A LEGISLATION RECENTLY SANCTIONED, IT IS PERTINENT TO STUDY THE CONSEQUENCES OF ITS APPLICABILITY. WITH THIS RESEARCH, IT IS EXPECTED TO PRESENT TO SOCIETY THE BENEFITS AND HARMS THAT THE REDUCTION OF BUREAUCRACY IN SUCH AN IMPORTANT PROCEDURE CAN CAUSE. FROM THIS PERSPECTIVE, THE DESCRIPTIVE METHOD WILL BE USED AS THE MAIN METHODOLOGY BY THE BIBLIOGRAPHIC SEARCH PROCEDURE.